LOCUS OF CONTROL DAN KINERJA KARYAWAN: UJI KOMPARASI - Suprayogi, Toteng Temy (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
This study aims to examine the relationship between locus of control and employee performance in a company in Jakarta. Using a sample of 54 employees (15 female and 39 male). This study tested the usefulness of locus of internal and external controls for explaining work performance using independent t-test. The results conclude that there is no difference in performance between employees who have a tendency to the locus of control internal with external, or in other words, the locus of control is not a factor that can explain the variation of performance. Limitations of the study and suggestions for future research are discussed. Keywords: locus of control, employee performance